2020
DOI: 10.3390/cancers12061398
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways and Targeted Therapies for Malignant Ovarian Germ Cell Tumors and Sex Cord–Stromal Tumors: A Contemporary Review

Abstract: Non-epithelial ovarian tumors are heterogeneous and account for approximately 10% of ovarian malignancies. The most common subtypes of non-epithelial ovarian tumors arise from germ cells or sex cord and stromal cells of the gonads. These tumors are usually detected at an early stage, and management includes surgical staging and debulking. When indicated for advanced disease, most respond to chemotherapy; however, options for patients with refractory disease are limited, and regimens can be associated with sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 161 publications
(294 reference statements)
0
19
0
Order By: Relevance
“…A previous study has shown that tyrosine modification plays a significant role in the regulation of gene expression and the therapeutic response of ovarian cancer [ 31 ]. Accordingly, from other previous studies, enrichment pathway analysis revealed that protein serine/threonine kinase activity could also participate in the therapeutic response of epithelial ovarian cancer [ 32 , 33 ]. Therefore, we can conclude that the AlkB family may be involved in the progression of OV by regulating protein posttranslational modification pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that tyrosine modification plays a significant role in the regulation of gene expression and the therapeutic response of ovarian cancer [ 31 ]. Accordingly, from other previous studies, enrichment pathway analysis revealed that protein serine/threonine kinase activity could also participate in the therapeutic response of epithelial ovarian cancer [ 32 , 33 ]. Therefore, we can conclude that the AlkB family may be involved in the progression of OV by regulating protein posttranslational modification pathways.…”
Section: Discussionmentioning
confidence: 99%
“…No consensus has been achieved on the best HDCT protocol, and the ongoing TIGER trial compares the conventional dose TIP chemotherapy (paclitaxel, ifosfamide, and cisplatin) with a TI-CE HDCT arm (paclitaxel and ifosfamide, followed by high-dose carboplatin and etoposide) in patients with advanced GCT. Recent genomic discoveries have uncovered the molecular landscape of some pediatric GCT [ 39 ]. Malignant germ cell tumors have a low mutational burden, but the KIT, KRAS, TGF-BMP, and Wnt-catenin signaling pathway inhibitors and anti-CD30 immunotherapy can be used as targeted therapies in patients with resistant disease.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate, prognosis, risk factors, and their molecular characteristics are outlined in Table 2 The most frequent mutations reported in OGCTs are KIT mutations and 12p amplification, which harbor KRAS [112]. The OGCT subtype, dysgerminomas harbor 12p amplification and KIT mutation at a frequency of 80% and 30-50%, respectively [116]. KIT is a proto-oncogene involved in PI3K/AKT/mTOR, JAK/ STAT and MAPK pathways [117], whereas the oncogene KRAS is involved in the tumor development pathway of Ras/Raf/MEK/ERK pathway [118].…”
Section: Ovarian Germ Cell Tumors (Ogcts)mentioning
confidence: 99%
“…The aneuploid, yolk sac tumors are reported to harbor PI3K and AKT1 mutations, besides KRAS altering PI3K/AKT/mTOR pathway. The TGFβ/BMP and Wnt/β-catenin signaling pathways are also reported to be activated in yolk sac tumors [116]. Few druggable targets of these pathways like AKT inhibitor (afuresertib) and MEK inhibitor (trametinib) are already under clinical trials for various OCs [119].…”
Section: Ovarian Germ Cell Tumors (Ogcts)mentioning
confidence: 99%